The incidence of hematuria in middle distance track running - Jones, G. R.; Newhouse, I. J.; Jakobi, J. M.; LaVoie, N.; Thayer, R. (Canadian Journal of Applied Physiology, 2001)
The purpose of this study was to establish if middle distance track athletes experience hematuria during their competitive season interval workouts and, if so, what type of workout based on intensity and distance was most associated with hematuria. During a 4-week observational period, athletes (n = 10) underwent reagent strip urinalysis before and after their twice weekly interval sessions. Positive samples for hematuria were analyzed microscopically to accurately determine red blood cell (RBC) loss. Seventy-one individual interval workouts were observed, of which 32 cases of hematuria were reported. Nine cases of hematuria exhibited >100 RBC per High Power Field (Hpf). Furthermore, 90% of the athletes experienced post-workout hematuria at least once. The highest incidence of hematuria was observed after workouts run at 110% of VáO2peak over short (600-1,500 m) to moderate (1,501-3,000 m) distances. All post-exercise cases of hematuria resolved within 2 hr of recovery.